Efficiency of photovoltaic conversion is improved reflective membrane - PU YI; ZHAI CAIJIN; YAN QIXU; DING LIMING (2018)
The utility model relates to a reflective membrane technical field, concretely relates to efficiency of photovoltaic conversion is improved reflective membrane, including the substrate layer and locate substrate layer lower floor the gluing layer, locate substrate layer upper strata microstructured layer, locate the reflector layer on microstructured layer upper strata, microstructured layer comprises a plurality of parallel arrangement's triangular prism series arrangement. The utility model discloses efficiency of photovoltaic conversion is improved reflective membrane can reduce the outer light of reflection photovoltaic glass, improves the solar energy utilization ratio. 本实用新型涉及反光膜技术领域，具体涉及种提高光伏转换效率的反光膜，包括基材层及设于基材层下层的胶黏层、设于基材层上层的微结构层、设于微结构层上层的反光层，微结构层由多个平行设置的三棱柱顺序排列组成。本实用新型提高光伏转换效率的反光膜可以减少反射光伏玻璃外的光线，提高太阳能利用率。